Classification of Slovenian Dry-Cured Ham – Kraški pršut – According to Texture Profile - Mateja Lušnic Polak; Tomaž Polak; Mojca Kuhar; Iva Zahija Jazbec; Tadej Kaltnekar; Lea Demšar (Polish Journal of Food and Nutrition Sciences)
The effects of the supplier and the mass of pork thighs together with some production parameters including mass loss during ham production, mass of the final products and relative content of non-protein nitrogen (NPN) on the texture profile of Slovenian dry-cured ham – Kraški pršut were investigated to determine its optimal texture. The study included 32 dry-cured hams from two mass classes (heavy with thigh mass at salting of 11.7–12.1 kg and light with thigh mass at salting of 10.5–10.7 kg) and two different pork thigh suppliers from regular production. Slices cut transversally from the thigh at approximately 8 cm from the femur head were used for physicochemical parameter (pH, contents of moisture, total fat, protein, NaCl, and NPN) analysis, instrumental texture analysis profile analysis (TPA), and sensory analysis. Pork thigh mass had a significant effect on the TPA parameters; light samples were harder, chewier, springier, more cohesive and resilient compared to the heavy samples. NaCl content and sensory scores for saltiness were higher in the light Kraški pršut samples than in the heavy ones. Based on the median for hardness in the sensory analysis, the samples were classified into three ranks of texture using linear discriminant analysis (9 variables, 100% correct classification): optimal (median 4.0; 19% of samples), slightly too soft (median 3.5, 72% of samples), and soft (median 3.0; 9% of samples). Kraški pršut mass and hardness were significantly correlated to saltiness, pastiness, aroma, and all TPA parameters (p≤0.05). Positive correlation (p≤0.05) was also observed between NPN and pastiness. These findings indicate the importance of supplier, mass of pork thighs, and production parameters for optimizing the texture of Kraški pršut.